Evaluation of stapler hepatectomy during a laparoscopic liver resection. Issue 11 (18th January 2013) - Buell, Joseph F.; Gayet, Brice; Han, Ho‐Seong; Wakabayashi, Go; Kim, Ki‐Hun; Belli, Giulio; Cannon, Robert; Saggi, Bob; Keneko, Hiro; Koffron, Alan; Brock, Guy; Dagher, Ibrahim
Abstract Methods An international database of 1499 laparoscopic liver resections was analysed using multivariate and Kaplan–Meier analysis. Results In total, 764 stapler hepatectomies (SH) were compared with 735 electrosurgical resections (ER). SH was employed in larger tumours (4.5 versus 3.8 cm; P < 0.003) with decreased operative times (2.6 versus 3.1 h; P < 0.001), blood loss (100 versus 200 cc; P < 0.001) and length of stay (3.0 versus 7.0 days; P < 0.001). SH incurred a trend towards higher complications (16% versus 13%; P = 0.057) including bile leaks (26/764, 3.4% versus 16/735, 2.2%: P = 0.091). To address group homogeneity, a subset analysis of lobar resections confirmed the benefits of SH. Kaplan–Meier analysis in non‐cirrhotic and cirrhotic patients confirmed equivalent patient (P = 0.290 and 0.118) and disease‐free survival (P = 0.120 and 0.268). Multivariate analysis confirmed the parenchymal transection technique did not increase the risk of cancer recurrence, whereas tumour size, the presence of cirrhosis and concomitant operations did. Conclusions A SH provides several advantages including: diminished blood loss, transfusion requirements and shorter operative times. In spite of the smaller surgical margins in the SH group, equivalent recurrence and survival rates were observed when matched for parenchyma and extent of resection.